Quiero Hablar Con Usted en Espanol, Juez: The Importance of Spanish at a Majority Hispanic Drug Court. (March 2016) - Frailing, Kelly; Carreon, Diana
We modified the participant perception survey utilized in the Multi-Site Adult Drug Court Evaluation and administered it to participants at a majority Hispanic drug court in south Texas. Results revealed generally positive perceptions of the judge and various measures of procedural justice. Results also revealed that participants perceived the ability to communicate with the (bilingual) judge in Spanish as important to their success in drug court and that this was true even of those participants who were fluent in English as well as Spanish. Our results generate an important policy consideration for these future courts, namely, the language abilities of the judge. We believe that judges at majority Hispanic drug courts will be most effective when they are bilingual in English and Spanish and we call on drug court planners to consider our findings as they develop new courts to serve this growing population.